Newborn screening for congenital hypothyroidism (CH) in early discharged infants - Domingo, Carmelita Fagela-
Rationale/Significance: The high cost of hospitalization resulting in the early discharge of newborn infants has led to the increasing use of 12-24 hour specimens for thryroid screening. Cost benefit analysis of data from the Philippine Newborn Screening Project shows that there are benefits to be gained if screening is done before the 24th hour of life. On the other hand, there are significant costs to cover if screening is done on the 48th hour or later in hospitalized newborns. #Objective: To determine the quantitative relationship between thyroid stimulating hormone (TSH) values taken on the 12th hour of life with those taken on the 48th to the 72nd hour. #Study Design: This is a cross sectional analytical study. #Participants and Methods : One thousand three hundred seventy (1370) full term normal infants delivered at the Philippine General Hospital and at the Rizal Medical Center from August 1999 to March 2001 participated in the study. Blood samples were collected by heel prick onto the prescribed filter paper for newborn screening at 12 to 24 hours of life and again at 48 to 72 hours in the same set of infants. Thyroid stimulating hormone (TSH) was determined by fluroimmunoassay using the auto delfia machine. #Results: The majority of participants (83%) came from Metro manila while the rest came from the provinces. Seven hundred thirty (53%) were males and 640 (46.7%) were females. Mean birth weight was 3013.5gm (SD=351.1) and mean birth length was 48.9cm. (SD=2.1). Fifty seven percent (57%) were delivered by caesarian section, 37.4% by vaginal route and 5.5% by outlet forceps extraction. Although there was a statistically significant association between TSH 12-24 and TSH 48-72 by Pearson correlation (R=0.326) as well as by simple regression (p,0.0001), the correlation was not clinically sufficient to predict level of TSH48-72. the use of transformed values for TsH did not significantly improve correlation. Sex and birth weight in relation to TSH48-72 showed a highly significant correlation by simple regression (p,0.05). Using a less stringent level of significance (p=0.02) to include all possible predictors multiple regression showed that sex and mode of delivery by casarean section (MODCS) were significant factors. There was significant interaction between birth weight and cesarean section but none between birth weight and outlet forceps extraction. The use of transformed values of TSH in the multiple regression did not improve the correlation coefficients. In this model mode of delivery by cesarean section (MODCS) and the factor of birth weight x cesarean section (BWCS) were significant (p,0.05). Further analysis showed that there are no omitted variables and that the data are heteroscedatic. #Conclusions: The quantitative relationship between TSH12-24 and TSH48-72 was found to be 0.326 which is statistically significant (p,0.0001). However, this magnitude of association is not clinically sufficient to predict TSH48-72. among the other factors that may affect TSH48-72, only sex and mode of delivery by cesarean section have been found to be statistically significant. Depsite its limitations, the 24-hour sample san be used for newborn screening especially with certain modifications like the use of age-adjusted criteria for TSH.
Vita.
Thesis (MS Clinical Epidemiology) -- University of the Philippines, Manila
Keywords: Neonatal screening; Hypothyroidism